Fundamentals of Database Indexing and Searching - Bhattacharya, Arnab (Boca Raton : CRC Press, 2015)
Fundamentals of database indexing and searching presents well-known database searching and indexing techniques. It focuses on similarity search queries, showing how to use distance functions to measure the notion of dissimilarity.After defining database queries and similarity search queries, the book organizes the most common and representative index structures according to their characteristics. The author first describes low-dimensional index structures, memory-based index structures, and hierarchical disk-based index structures. He then outlines useful distance measures and index structures that use the distance information to efficiently solve similarity search queries. Focusing on the difficult dimensionality phenomenon, he also presents several indexing methods that specifically deal with high-dimensional spaces. In addition, the book covers data reduction techniques, including embedding, various data transforms, and histograms.Through numerous real-world examples, this book explores how to effectively index and search for information in large collections of data. Requiring only a basic computer science background, it is accessible to practitioners and advanced undergraduate students--
1. Basics -- 2. Low-dimensional index structures -- 3. Disk-based index structures -- 4. Distances -- 5. High-dimensional spaces -- 6. Data reduction techniques.
Includes bibliographical references and index.
Also available in print format.
Keywords: File organization (Computer science); Database management; Querying (Computer science); Database searching; Indexing; Electronic books